2022
DOI: 10.1002/ece3.8626
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography and population genetic structure of the European roe deer in Switzerland following recent recolonization

Abstract: In the early 1800s, the European roe deer (Capreolus capreolus) was probably extirpated from Switzerland, due to overhunting and deforestation. After a federal law was enacted in 1875 to protect lactating females and young, and limiting the hunting season, the roe deer successfully recovered and recolonized Switzerland. In this study, we use mitochondrial DNA and nuclear DNA markers to investigate the recolonization and assess contemporary genetic structure in relation to broad topographic features, in order t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…Consequently, a key goal in the management of newly reestablished or fragmented populations is to maximize the genetic diversity and minimize drift and inbreeding (Frankham et al, 2017 ). Several studies have shown that genetic diversity in reintroduced and naturally recolonized populations is often higher in those that receive gene flow from other populations (Biebach & Keller, 2012 ; Latch & Rhodes, 2005 ; Malaney et al, 2018 ), originate from multiple source populations (Huff et al, 2010 ; Sasmal et al, 2013 ; Vasiljevic et al, 2022 ; Williams et al, 2000 ; Williams & Scribner, 2010 ) and in reintroductions that use multiple translocations (Cullingham & Moehrenschlager, 2013 ; Drauch & Rhodes, 2007 ). Without such mitigating factors, erosion of genetic diversity and accumulation of inbreeding can occur due to isolation and/or slow population growth (Hundertmark & van Daele, 2010 ; Williams et al, 2002 ), and may have detrimental population‐level consequences for fitness‐related traits (Wisely et al, 2008 ) and population growth rates (Bozzuto et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a key goal in the management of newly reestablished or fragmented populations is to maximize the genetic diversity and minimize drift and inbreeding (Frankham et al, 2017 ). Several studies have shown that genetic diversity in reintroduced and naturally recolonized populations is often higher in those that receive gene flow from other populations (Biebach & Keller, 2012 ; Latch & Rhodes, 2005 ; Malaney et al, 2018 ), originate from multiple source populations (Huff et al, 2010 ; Sasmal et al, 2013 ; Vasiljevic et al, 2022 ; Williams et al, 2000 ; Williams & Scribner, 2010 ) and in reintroductions that use multiple translocations (Cullingham & Moehrenschlager, 2013 ; Drauch & Rhodes, 2007 ). Without such mitigating factors, erosion of genetic diversity and accumulation of inbreeding can occur due to isolation and/or slow population growth (Hundertmark & van Daele, 2010 ; Williams et al, 2002 ), and may have detrimental population‐level consequences for fitness‐related traits (Wisely et al, 2008 ) and population growth rates (Bozzuto et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%